An IoT Based Approach to Monitor and Replace Batteries for Battery Operated Vehicle. Issue 1 (December 2020) - Kaushal, Rajesh Kumar; Panda, Surya Narayan; Kumar, Naveen
Abstract: In today's world of constant connectivity, instant gratification and customer-driven market, immediate availability of battery supply warehouses and replacement are the vast array of challenges faced by the vehicles such as e-rickshaws. Eelectric vehicles, as a new generation of vehicles, are increasingly favoured by the automotive research field because of their incomparable advantages in energy saving and emission reduction and reduction of human dependence on traditional fossil resources. Especially in the issue of safe operation and supervision of electric vehicles, it has received special attention. Therefore, remote monitoring and management of electric vehicles and remote monitoring of battery replacement stations have become an important part of the safe operation of electric vehicles. In the traditional approach, the recharging pattern of batteries of the e-rickshaw drivers is their own household sockets but the proposed system can immediately provide charged batteries and replace the used batteries by tracking the battery life along with storing the necessary data in the cloud so that it can be accessed from anywhere.